Location-specific expression of chemokines, TNF-α and S100 proteins in a teat explant model. Issue 3 (April 2015) - Lind, Monique; Sipka, Anja S; Schuberth, Hans-Joachim; Blutke, Andreas; Wanke, Rüdiger; Sauter-Louis, Carola; Duda, Katarzyna A; Holst, Otto; Rainard, Pascal; Germon, Pierre; Zerbe, Holm; Petzl, Wolfram
The distal compartments of the udder are the first to interact with invading pathogens. The regulatory and effector functions of two major teat regions [Fürstenberg's rosette (FR); teat cistern (TC)] are largely unknown. The objective of this study was to establish an in vitro model with explants of the FR and the TC to analyse their response towards Escherichia coli LPS and Staphylococcus aureus lipoteichoic acid (LTA). Quantitative stereological analysis confirmed differences in the cellular composition of FR and TC explants. Chemokine (CXCL8, CCL5, CCL20) and TNF-α mRNA were expressed at low levels in both locations. Explant stimulation with LPS increased the mRNA abundance of all tested chemokines and TNF-α. Stimulation with LTA only induced CCL20 and CXCL8. LPS- and LTA-stimulated explant supernatants contained CXCL8 and CXCL3. Supernatants significantly attracted neutrophils in vitro . Compared with TC, the FR showed high constitutive mRNA expression of S100 proteins (A8, A9, A12). In the TC, both LPS and LTA significantly induced S100A8, whereas S100A9 and S100A12 expression was only induced by LPS. The novel model system underpins the role of the teat for recognising pathogens and shaping a pathogen- and location-specific immune response.